Vacuum-Ultraviolet Absorption Spectra of Icy C2H4 at 13–60 K - Lo, Jen-Iu; Ghosh, Rana; Lu, Hsiao-Chi; Hung, Wei-Hsiu; Cheng, Bing-Ming (Frontiers in Astronomy and Space Sciences, 2021)
The thermal variation of absorption spectra of icy ethene in wavelength range 105-220 nm was measured from 13 K to 100 K using a synchrotron as light source. Sublimation of icy ethene began above 62 K, resulting in decreasing absorption. The absorption of icy ethene increased at wavelengths less than about 150 nm with increasing temperature from 13 K to 60 K, but decreased beyond above 150 nm. According to detailed examination, the absorption spectra of icy ethene intersected at isosbestic point 147.0 nm from 13 K to 17 K, whereas those varied absorption profiles crossed at another point, 150.6 nm, from 23 K to 60 K. These results indicate that ethene ices might exhibit three structures within temperature range 13-60 K. This work enhances our understanding of the spectra of icy ethene at low temperatures and our knowledge of its astrochemistry and astrophysics in cold astro-environments